Knowlegde Spillovers, absorptive capacity and growth: An industry-level Analysis for OECD countries - Ioannis Bournakis; Dimitris Christopoulos; Sushanta Mallick (FIW - Research Centre International Economics, 2015)
Spillovers have usually been undertaken at the country level, the spillover effects can be more definitive only if the analysis is conducted at the industry-level. This paper therefore attempts to identify spillovers by disentangling technological innovations into intra- and inter-national knowledge innovations at industry level in driving per capita output growth. Our main findings are first, that there is evidence for a robust positive relationship between R&D, human capital and output growth across these countries at industry-level. Second, the potential of international spillover gains is greater in countries with higher human capital and in industries whose pattern of production is more R&D oriented, import intensive, and dependent on vertical FDI. Finally, significant heterogeneity is found between high and low-tech industries with high-tech group displaying greater knowledge spillovers, suggesting that low-tech industries need to be more innovative in order to absorb the technological advancements of domestic and international rivals.
Keywords: F1; F6; O3; O4; 330; Knowledge spillover; Industry-level productivity; R&D